EFFECT OF DEXTRIN CONCENTRATION AND DRYING TIME ON THE PHYSICAL, CHEMICAL AND ORGANOLEPTIC CHARACTERISTICS OF MUSHROOM BROTH POWDER - Dego Yusa Ali; Bella Ayu Shafira; Yunianta Yunianta (Jurnal Pangan dan Agroindustri, 2021)
Â Several types of mushrooms such as white oyster mushrooms, shiitake and straw have a protein content with a high proportion of glutamic acid so that they can be utilized as broth powder. The purpose of this study was to determine the interaction of dextrin concentration and drying time and the best treatment on the physicochemical and organoleptic characteristics of mushroom broth powder. The study used the factorial Randomized Block Design (RBD) method, where the first factor was dextrin concentration (7.50%, 12.50%, 17.50%) and the second factor was drying time (8 hours, 10 hours, 12 hours). The data were analyzed by using ANOVA and further tests used LSD or DMRT. The organoleptic test was carried out by using the Hedonic Scale Scoring test and the best treatment was chosen by using the Zeleny method. The results showed the addition of dextrin concentration and drying time gave significant interactions to the water content, water vapor absorption and yield. The best treatment was obtained in broth powder with a dextrin concentration of 7.50% and a drying time of 8 hours.